PENDAMPINGAN PENGELOLAAN KEUANGAN BAGI MASYARAKAT DESA WISATA KAMPUNG BAMBU DESA BANYURESMI PANDEGLANG - Asih Machfuzhoh; Enok Nurhayati; Emma Suryani (Universitas Muhammadiyah Malang, 2020)
Digital marketing can help a lot of tourism practitioners, especially the Tourism Village in marketing the tourism village. Along with changes in people's behavior that is more 'internet', the internet media is an effective media in marketing tourism services. Since not all rural communities are familiar with digital marketing, there is a need for community empowerment to develop their Tourism Village through Digital Marketing Management activities.The method of carrying out the dedication by making a program of empowering the skills of tourism aware groups, and also the community of Banyuresmi Village, Jiput Pandeglang. It is hoped that after this program, the community and also POKDARWIS can effectively manage digital marketing (product, price, place, promotion) to develop Kampung Bambu Tourism Village.